Securing an optimum operating field without undesired tissue damage in neurosurgery. (1st October 2016) - Fukuhara, A.; Tsujita, T.; Sase, K.; Konno, A.; Nakagawa, A.; Endo, T.; Tominaga, T.; Jiang, X.; Abiko, S.; Uchiyama, M.
Graphical Abstract: Abstract : In neurosurgery, surgeons sometimes retract brain tissue to prepare an operating field around a lesion. In addition, they are required to plan a safe surgical pathway for deep-brain regions while considering tissue damage caused by excessive stress. The goal of this study is to develop a technique for automatically generating a surgery pathway for lesions in the deep-brain region, focusing on securing an operating field around the lesion as a first step and also considering brain tissue deformation. In previous studies, securing the operating field has been treated as a single-objective optimization problem in order to maximize the viewable area of the lesion. However, in this study, the task of securing the operating field is formulated as a multi-objective optimization problem. Using a technique that combines finite element analysis and an optimization method, the principal stress on the brain is constrained to less than a certain threshold value, and the position and orientation of the surgical instrument are optimized for safe retraction of the brain according to various weighting factors.